PERILAKU DAN KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP NIAT BERTRANSAKSI SECARA ONLINE DI SHOPEE - Kisthi Hanila Dewi (EKBIS (Ekonomi & Bisnis), 2023)
The development of e-commerce has experienced rapid growth in Indonesia, and Shopee is one of the leading e-commerce platforms in the country. The purpose of this study was to determine consumer buying behavior and decisions on the intention to transact online at Shopee. Quantitative research methods with sampling techniques using purposive sampling, the research sample is respondents who have made purchases on the shopee platform. The results showed that 72.4% of behavior and purchasing decisions had an effect on transaction intentions at shopee. To increase transactions at Shopee, you can offer competitive prices and attractive discounts for products at Shopee to attract consumer attention and encourage consumers to repurchase.